Content Area Reading: Principles and Strategies to Promote Independent Learning - Bachrudin Musthafa (TEFLIN Journal: A publication on the teaching and learning of English, 1997)
Abstract: Since the formal education cannot be expected to provide individuals with sufficient knowledge to last a lifetime, educators need to help learners develop knowledge, skills, and predispositions essential for independent learning. Reading in content areas whose primary purpose is to help learners acquire content literacy or the ability to use reading (and) writing for the acquisition of new knowledge from materials required in their subject is one way of preparing students to be independent learners.